Students' Mathematical Concept Understanding in Introductory Mathematics Course - Putri Yulia; Eline Yanty Putri Nasution (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2022)
The Introductory Mathematics Course is an initial course that students must master before they study advanced courses. However, many students still need higher grades in this course. This study aims to analyze the students' mathematical concepts understanding in Introductory Mathematics Course. This study is a descriptive qualitative study involving three mathematics education students at an Islamic University in Jambi. Each has high, medium, and low abilities based on the mathematical concept of understanding test results. The students were also interviewed to confirm their test answers. Data were analyzed descriptively using the method-triangulation. The results of this study indicate that, in general, the students' mathematical concepts understanding in Introductory Mathematics Course is in the medium category. A student with high ability can answer all the questions correctly, while ones with medium and low abilities still need to correct some things. The students with medium and low abilities must train more and get used to working on concept-understanding questions. Learning methods are also needed that further hone their ability to understand mathematical concepts.